Dual-task performance and balance in patients with severe COPD: a cross-sectional study - Crisan Alexandru Florian; Pescaru Camelia Corina; Maritescu Adelina; Carunta Vlad; Onofrei Roxana Ramona; Stoicescu Emil Robert; Oancea Cristian (Therapeutic Advances in Respiratory Disease)
Background: Chronic obstructive pulmonary disease (COPD) significantly impacts respiratory and motor function, balance, and cognition, leading to muscle weakness and impaired exercise capacity. The impairments often result in challenges with daily activities, particularly those requiring dual-tasking. Objectives: The study investigated whether patients with severe COPD would exhibit more significant cognitive and motor performance decline during dual tasks compared to healthy controls. Design: This study employed a cross-sectional design to compare cognitive and motor performance in dual tasks between patients with severe COPD and healthy controls. Methods: We included 44 patients with severe COPD and 43 healthy individuals. Participants underwent various tests, including pulmonary function tests, six-minute walking tests, dual Timed Up and Go tests (TUG), dual single-leg stance tests (SLS), Berg Balance Scale assessments, and Falls Efficacy Scale International evaluations (FES-I). Results: The COPD group had significantly lower scores in the Berg Balance Scale (BBS; 44.79 ± 4.70 vs 52.67 ± 2.16, p  < 0.0001) and longer times for the TUG test (12.44 s; [11.44, 13.50] vs 9.14 s; [7.91, 10.11], p  < 0.0001) and shorter times for the SLS test (14.15 s; [12.31, 15.65] vs 26.20 s; [23.45, 30.88], p  < 0.0001), indicating poorer functional mobility and balance. Furthermore, dual-task interference (DTI) outcomes revealed poorer performance in the COPD group ( p  < 0.0001). The fear of falling (FES-I) was increased in the COPD group. There was a significant positive correlation between DTI TUG and FES-I ( r  = 0.35, p  = 0.01) and a negative correlation between DTI SLS and BBS ( r  = −0.41, p  = 0.005) in the COPD group. Conclusion: The study reveals significant impairments in DTI and balance among patients with severe COPD. Patients with severe COPD performed worse in tests involving dual tasks. They had poorer balance overall compared to healthy controls, with longer times for the dual Timed Up and Go test and shorter times for the SLS test, indicating a higher susceptibility to DTI and a greater fear of falling.